Improved Carbon and Nitrogen Isotopic Ratios for CH3CN in Titan’s Atmosphere Using ALMA - Jonathon Nosowitz; Martin A. Cordiner; Conor A. Nixon; Alexander E. Thelen; Zbigniew Kisiel; Nicholas A. Teanby; Patrick G. J. Irwin; Steven B. Charnley; Véronique Vuitton (The Planetary Science Journal)
Titan, Saturn’s largest satellite, maintains an atmosphere composed primarily of nitrogen (N _2 ) and methane (CH _4 ) that leads to complex organic chemistry. Some of the nitriles (CN-bearing organics) on Titan are known to have substantially enhanced ^15 N abundances compared to Earth and Titan’s dominant nitrogen (N _2 ) reservoir. The ^14 N/ ^15 N isotopic ratio in Titan’s nitriles can provide better constraints on the synthesis of nitrogen-bearing organics in planetary atmospheres as well as insights into the origin of Titan’s large nitrogen abundance. Using high signal-to-noise ratio (>13), disk-integrated observations obtained with the Atacama Large Millimeter/submillimeter Array Band 6 receiver (211–275 GHz), we measure the ^14 N/ ^15 N and ^12 C/ ^13 C isotopic ratios of acetonitrile (CH _3 CN) in Titan’s stratosphere. Using the NEMESIS, we derived the CH _3 CN/ ^13 CH _3 CN ratio to be 89.2 ± 7.0 and the CH _3 CN/CH _3 ^13 CN ratio to be 91.2 ± 6.0, in agreement with the ^12 C/ ^13 C ratio in Titan’s methane and other solar system species. We found the ^14 N/ ^15 N isotopic ratio to be 68.9 ± 4.2, consistent with previously derived values for HCN and HC _3 N, confirming an enhanced ^15 N abundance in Titan’s nitriles compared with the bulk atmospheric N _2 value of ^14 N/ ^15 N = 168, in agreement with chemical models incorporating isotope-selective photodissociation of N _2 at high altitudes.